Enhancing Vocabulary Mastery Through English Songs: In the Eyes of EFL Students - Sayit Abdul Karim; Suryo Sudiro; Dina Rizki Annisa; Hana I Khairunnisa; Dyah Ayu Rahmawati (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
The present study attempts to explore EFL students’ perceptions of utilizing English songs to enhance students’ vocabulary mastery. The present study employs a qualitative descriptive research design and the data were gathered by administering an online survey using a questionnaire through Google Forms as the research instrument. 56 (39 females and 17 males) EFL students from Universitas Teknologi Yogyakarta were involved in the present study.Apart from the questionnaire, an online semi-structured interview with 6 respondents using the Whatsapp application was also conducted to further explore their views about how English songs could improve their vocabulary mastery. Furthermore, there are five questions that respondents should be filled out in the online google form using the 4 Likert Scale, ranging from the lowest point 1 (strongly disagree) to the highest point 4 (strongly agree). The interview was conducted to further explore their perceptions of how the English songs enrich their vocabulary mastery. The findings revealed that 46,6% of respondents strongly agree and 44,6% agree that they would look up the meaning of the song's lyrics given. Furthermore, 50% of the respondents strongly agree and 41.1% of them agree about English songs facilitate them to learn English. Meanwhile, 42,9% of the respondents strongly agree and 41,1% agree about English songs as an interesting media of learning, therefore, they utilized the songs to enhance their vocabulary achievement. The results of the interview respondents revealed six respondents (MZ, KF, PL, AF, SF, and GT) perceived that the utilization of songs in their learning brings a positive impact on their English language vocabulary development. However, two respondents, DL and GT viewed that English songs have both advantages and disadvantages for some reasons.